The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1088/0953-4075/42/14/145304
|View full text |Cite
|
Sign up to set email alerts
|

Finite temperature correction to the Thomas–Fermi approximation for a Bose–Einstein condensate: comparison between theory and experiment

Abstract: We observe experimentally a deviation of the radius of a Bose–Einstein condensate from the standard Thomas–Fermi prediction, after free expansion, as a function of temperature. A modified Hartree–Fock model is used to explain the observations, mainly based on the influence of the thermal cloud on the condensate cloud.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
4
19
0
1
Order By: Relevance
“…There is an agreement with Castin-Dum predictions [9] for low temperatures, however, when the temperature gets higher the ratioR 5 /N 0 departs from the Castin-Dum value getting larger (see Fig. 4 of [12]). The authors explain this behavior by us- ing a combination of a modified Hartree-Fock model to describe the condensed and thermal fractions in a trap and an expansion model formulated by Castin and Dum [9].…”
supporting
confidence: 83%
“…There is an agreement with Castin-Dum predictions [9] for low temperatures, however, when the temperature gets higher the ratioR 5 /N 0 departs from the Castin-Dum value getting larger (see Fig. 4 of [12]). The authors explain this behavior by us- ing a combination of a modified Hartree-Fock model to describe the condensed and thermal fractions in a trap and an expansion model formulated by Castin and Dum [9].…”
supporting
confidence: 83%
“…the integrated value of the anomalous density[22]. The relation (11.a) reproduces the overall behavior observed experimentally in[61] as well as yielding the zero temperature expression for 1 both theoretical treatments of HFB-Popov and experimental results of[61] for small values of β .Furthermore, despite the lack of experimental data of the anomalous density in the literature, we can point out from expression (11.b) that the radius of the anomalous density is small compared to that of the condensate at low temperature. At high temperature both radii should vanish since 0 the condensed fraction.…”
supporting
confidence: 75%
“…To give an example, we can mention the theory of an expanding Bose gas at finite temperatures proposed in [2]. Comparison of the theory [2] with three experimental studies of an expanding two-component gas [3][4][5] revealed contradictions between the experimental and theoretical results.The comment also contains a number of statements that are difficult to agree with. The authors of the comment erroneously believe that our estimate of the accuracy (1.8%) refers to the description of expansion of the condensed fraction in a two-component Bose gas.…”
mentioning
confidence: 99%
“…To give an example, we can mention the theory of an expanding Bose gas at finite temperatures proposed in [2]. Comparison of the theory [2] with three experimental studies of an expanding two-component gas [3][4][5] revealed contradictions between the experimental and theoretical results.…”
mentioning
confidence: 99%